Third-Order Nonlinear Optical Properties of Hibiscus Sabdariffa Dye Using Z-scan Method - Binti Juma'in, Ainna syafiqah; Nurul Nadia Adnan; Ganesan Krishnan (Enhanced Knowledge in Sciences and Technology, 2024)
This study delves into the characterization of nonlinear optical properties of Hibiscus Sabdariffa Roselle through the application of the Z-scan method. Molecular vibration properties were determined using Fourier-transform infrared-ray spectroscopy (FTIR), which aids in identifying chemical bonds by generating an infrared absorption spectrum. Additionally, the absorbance spectrum of the sample was measured using UV-vis Spectroscopy. The research focused on elucidating the nonlinear susceptibility χ³ and intensity-dependent refractive index n2 of Hibiscus Sabdariffa dye solutions within the nanosecond domain at 532 nm. The experimental approach employed Z-scan and optical limiting techniques to quantify the changes in n₂, nonlinear absorption coefficient (β), and the real and imaginary parts of χ³ concerning the concentration of the natural dye extract. The findings revealed that nonlinear refraction played a pivotal role in shaping the third-order nonlinearity of Hibiscus Sabdariffa dye solutions. This effect led to a substantial optical limiting behavior, showcasing the potential of Hibiscus Sabdariffa as a candidate for nonlinear optical applications. The outcomes of this study contribute valuable insights into the third-order nonlinear optical properties of natural dye extracts and their applicability in optical limiting devices.